Artificial Intelligence in Islamic Financial Institutions in Indonesia: A Systematic Literature Review - Maulani, Subhan; Rakhmawati, Aneta; Budiman, Mochammad Arif; Sadewa, Manik Mutiara; Ainun, Basyirah (International Journal of Economics, Business Management and Accounting (IJEBMA), 2025)
Artificial intelligence is an innovation and development of computers and machines that create human-like capabilities, namely, cognitive abilities, learning, adaptation, and decision making. The implementation of artificial intelligence in Islamic financial institutions increases not only for service innovation but also for analyses data, fraud detection systems, and analyses risk management. The key to dealing with technological change is the collaboration of various parties, namely, practitioners, academics, industry players, regulators, and experts in Islamic finance and economics. This study aims to determine the trend of publication, application, development, challenges and opportunities of artificial intelligence in Islamic financial institutions in Indonesia from 2014 to 2023. The results obtained in this study show that there are 15 journal articles that show 5 types of artificial intelligence in Islamic financial institutions, namely, financial technology, digital security, blockchain, robo-advisors, and digital banks. Islamic financial institutions in Indonesia have used artificial intelligence as needed. The development of artificial intelligence has changed people's life style, increased human resources, and developed regulations to increase security and trust. The challenge is to increase innovation, supervision and protection, create maximum literacy and inclusion, and collaboration. The opportunities that occur are the creation of a sustainable economy, increasing the development of Islamic economics and finance, creating superior human resources, and easy to analyse risk management